Analysis of the Implementation of Distance Learning in the COVID-19 Pandemic New Normal Era - Muzanip Alperi; Riyanto Riyanto; Johanes Sapri; Alexon Alexon; Dewi Handayani (International Journal of Asian Education, 2021)
This research was conducted to see the implementation of distance learning during the New Habitual Adaptation (NHA) period of the COVID 19 pandemic. The indicators that will be seen are planning, implementation, problems, and solutions of distance learning. The method used in this research is a qualitative analysis method. The results of this study are(1) Learning planning for NHA mass education units in Kepahiang Regency has prepared related regulations, and an education unit ordinance has been issued related to its implementation. The infrastructure to prevent COVID 19 in the Kepahiang District education unit is also excellent. Therefore, the lesson plan that has been prepared has also been adjusted to the NHA period. (2) The implementation of AKB learning in Kepahiang Regency was actively followed by more than 80% of students, the most widely used learning method was offline distance, and the most widely used media was WhatsApp. (3) Obstacles faced in the learning process of the NHA period in the Kepahiang Regency are the facilities, networks, competencies, and complexity of the student's brain. (4) Solution options offered and carried out are offline distance learning. This research is essential because there are instruments whose indicators are determined according to the objectives achieved.